2015
DOI: 10.3390/en81212429
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Impact of Initial Moisture Content in Oil Impregnated Insulation Paper on Thermal Aging Rate of Condenser Bushing

Abstract: This paper studied the impact of moisture on the correlated characteristics of the condenser bushings oil-paper insulation system. The oil-impregnated paper samples underwent accelerated thermal aging at 130˝C after preparation at different initial moisture contents (1%, 3%, 5% and 7%). All the samples were extracted periodically for the measurement of the moisture content, the degree of polymerization (DP) and frequency domain dielectric spectroscopy (FDS). Next, the measurement results of samples were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Wang et al [7] investigated the influence of initial moisture contents in oil impregnated paper of the condenser bushing. The results of their experience indicated that the initial moisture content has appreciable impact on the degradation of the insulation paper during the initial aging period.…”
Section: A Review Of the Special Issuementioning
confidence: 99%
“…Wang et al [7] investigated the influence of initial moisture contents in oil impregnated paper of the condenser bushing. The results of their experience indicated that the initial moisture content has appreciable impact on the degradation of the insulation paper during the initial aging period.…”
Section: A Review Of the Special Issuementioning
confidence: 99%
“…A simplified HV bushing structure [21][22][23], as shown in Figure 2a, was set up. This structure consisted of three layers from the outside to the inside.…”
Section: Specimenmentioning
confidence: 99%
“…So, the characteristic Sm is modified to eliminate the influence of aging degree. The modified Sm is as shown in Equation (8). In Equation (8), λ is the increased value of Sm caused by the aging degree in insulating paper relative to the unaged insulating paper in frequency 10 1~1 0 3 Hz.…”
Section: Aging Compensation Factormentioning
confidence: 99%
“…So, the characteristic S m is modified to eliminate the influence of aging degree. The modified S m is as shown in Equation (8).…”
Section: Aging Compensation Factormentioning
confidence: 99%
See 1 more Smart Citation